Intrinsic AuPt-alloy particles decorated on TiO2 nanotubes provide enhanced photocatalytic degradation. (1st December 2018) - Sanabria-Arenas, Beatriz Eugenia; Mazare, Anca; Yoo, Jeongeun; Nguyen, Nhat Truong; Hejazi, Seyedsina; Bian, Haidong; Diamanti, Maria Vittoria; Pedeferri, Maria Pia; Schmuki, Patrik
Abstract: In this study we investigate the performance of noble metal co-catalysts on anodic TiO2 nanotubes for the photocatalytic degradation of a model pollutant. We create the noble metal decoration (nanoparticles of Au, Pt and mixed AuPt) intrinsically and extrinsically. Intrinsic decoration is achieved using a noble metal containing titanium alloy for anodic tube growth. Extrinsic decoration is carried out by physical vapor deposition (PVD) of the same noble elements on pure titania tubes. We find the AuPt intrinsic decoration to provide a significant enhancement for the photocatalytic decomposition of the model pollutant acid orange 7 (AO7) due to a synergistic effect in the formed AuPt alloy. The AuPt alloy provides a photocatalytic activity that is higher than comparable extrinsic decoration or single element (Pt or Au) intrinsic decoration. Graphical abstract: Highlights: AuPt alloy particles can intrinsically be decorated on anodicTiO2 nanotubes. Anodization is carried out using AuPtTi alloys. Alternatively extrinsic noble metal decoration is done by sputter-dewetting. The photocatalytic activity for intrinsically decorated tubes is significantly higher than for extrinsic decoration.